Cash-in-hand, benefit fraud and unemployment insurance - Ian W. Long; Vito Polito (Cardiff University, Cardiff Business School, 2015)
Recent evidence questions the nature of the re-employment spike as unemployment insurance (UI) payments expire. Unemployed agents do not appear to devote more time to search and are observed leaving the UI scheme early without necessarily entering employment. We show that benefit fraud is consistent with both observations. Over time, UI recipients become increasingly willing to accept short-term cash-in-hand work. This takes them away from job search. Im- mediately before UI expiry, the risk of punishment for fraud exceeds the value of remaining payments. Recipients may voluntarily leave the scheme to accept cash-in-hand opportunities.
Keywords: J46; J64; J65; K42; 330; Cash-in-hand; Benefit fraud; Unemployment insurance; Re-employment spike